FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA LANJUT USIA DI WILAYAH KERJA PUSKESMAS KAMPAR - Nurhapipa Nurhapipa; Winda Septiani; Siska Nasastra P.M (Ensiklopedia Sosial Review, 2022)
: Nutritional Status is a component consisting of several food inputs to the nutritional adequacy that can be seen by using the body mass index. Balanced nutrition for elderly should be applied by looking at the condition, whether it can still chew well or not. Data coverage of elderly nutrition in Kampar district is 20.8%, from 32 Puskesmas in Kampar District, which experienced the lowest elderly nutritional status of Kampar Puskesmas, 19.8% with the number of visits 425 elderly patients in 2018. This research aims to determine the relationship of nutritional status factor in the elderly in Kampar Health care area year 2019. This type of quantitative research with cross sectional design. The population of the study was all elderly patients in the KAMPAR health care work area as much as 425 elderly people with a sample of 186 respondents. Sampling techniques are purposive sampled. Research instruments using questionnaires. Data analysis is carried out univariate and bivariate with the chi-square test (α = 0.05). The results of bivariate analysis obtained there is a significant relationship between the diet (ρ = 0.031 ˂ α = 0.05), knowledge (ρ = 0.022 ˂ α = 0.05), physical activity (ρ = 0.009 ˂ α = 0.05), and the role of the health officer (ρ = 0.004 ˂ α = 0.05) with elderly nutritional status. Can be deduced ability, diet, knowledge, physical activity, the role of health peugas with the status of elderly nutrition. Based on the results of the study, the advice for Kampar community health care is expected to conduct an outreach program related to healthy eating, counseling about the necessary food that must be restricted to be consumed by the elderly, and Reduce physical activity in its work do not weigh and affect its health.   Keywords: Elderly nutritional Status Puskesmas Kampar, die knowledge, activity Physical.